How does the impact of the COVID-19 pandemic on Indonesia's Islamic stock returns? - Agustin, Isnaini Nuzula (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2021)
The unprecedented COVID-19 pandemic has ripped down the worldwide economies since the beginning of 2020. The stock market was one of the economic sectors that experienced depression and crashed during the pandemic. In this study, we mount an investigation on how Indonesia's large-scale social restrictions (known as "PSBB"), the announcement of the daily growth in total confirmed and death cases by COVID-19 affect the dynamic of Islamic stock returns in the Jakarta Islamic Index. This study used panel regression to test the effect between variables with market-to-book ratio and market capitalization ruled as a control variable. This study concluded that the announcement of daily growth in total confirmed cases by COVID-19 and the implementation of PSBB has a negative effect on the deterioration of the Islamic stock market's stability. Therefore, the higher growth of the total confirmed cases by COVID-19 and the tightening of the PSBB that was announced and implemented by the government would impact on the volatility of market and shareholders returns negatively. Interestingly, this study also found that there was a positive and significant relationship between the daily growth of death cases and stock return. Furthermore, the sectors of consumer goods, mining, and trading counted as the most performed market during the pandemic crisis.